Preparation and characterization of low CTE thermoplastic copolyimide resins based on the structural design of block sequence - Wu, Gaojie; Qi, Shengli; Tian, Guofeng; Wu, Dezhen (European polymer journal, 2023)
[Display omitted] •Two series of random or block copolyimide resins were prepared using BPDA and TFMB as rigid components, ODPA and DDS as flexible components.•The effect of monomer ratios, block copolymerization and block chain lengths on thermoplastic processability and thermal dimensional stability was investigated.•The PI-B343 resin with suitable block chain lengths showed excellent thermoplastic processability and low CTE.•Thermoplastic processability and thermal dimensional stability were innovatively decomposed into two levels based on the motility of different structural units to achieve simultaneous regulation of the two properties. In order to solve the challenge of balancing the thermoplastic processing properties and thermal dimensional stability of polyimide (PI) resin, in this research, 3,3′,4,4′-biphenyl tetracarboxylic diandhydride (BPDA) and 2,2′-bis(trifluoromethyl)benzidine (TFMB) were used as rigid components, 4,4′-oxydiphthalic anhydride (ODPA) and 4,4′-diaminodiphenyl sulfone (DDS) as flexible components. A series of random copolyimide resins was prepared by adjusting the molar ratio of rigid and flexible monomers. Determining the molar ratio which could balance the thermoplastic processing properties and thermal dimensional stability, block copolyimide resins with different rigid and flexible block lengths were then prepared in this ratio. The research showed that the molar ratio of monomers and the sequence structure of molecular chains had a strong influence on the performance of PI resins. When the content or block length of rigid component increased, the coefficient of thermal expansion (CTE) decreased but the glass transition temperatures (Tg) and melt viscosity increased. The PI-B343 resin had a CTE value of 40.63 ppm/K and the lowest melt viscosity reached 675 Pa·s, achieved the simultaneous regulation of the thermoplastic processing properties and thermal dimensional stability for PI resin.